Small Cell and Squamous Cell Carcinomas of the Head and Neck: Comparing Incidence and Survival Trends Based on Surveillance, Epidemiology, and End Results (SEER) Data - Bean, Marta B. (Oncologist, 2019)
BACKGROUND. Small cell carcinomas of the head and neck (SmCCHNs) are rare neoplasms with an unfavorable prognosis. Population‐based data describing survival and prognostic factors for SmCCHN are limited. METHODS. Data were obtained from the U.S. National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database for 1973–2013. Patient and tumor‐related characteristics for SmCCHN were compared with those for squamous cell carcinoma of the head and neck (SCCHN). Survival was compared by constructing Kaplan‐Meier curves and Cox proportional hazard models with and without propensity score matching. RESULTS. The data set included 609 SmCCHN and 227,943 SCCHN cases. Both histological subtypes were more common in men than women and more common in white patients. SmCCHN was most likely to originate in the larynx, glottis and hypopharynx, or salivary glands and to present with more advanced stage and grade. SCCHN was most likely to originate in the oral cavity and was found infrequently in the salivary glands. Overall 5‐ and 10‐year survival estimates were 27% and 18% for SmCCHN and 46% and 31% for SCCHN, respectively. In multivariable survival analyses adjusting for age, sex, race, marital status, year of diagnosis, stage, grade, and receipt of radiation, the hazard ratio (HR) comparing SmCCHN with SCCHN was 1.53 with a 95% confidence interval (CI) from 1.39 to 1.68. Average 5‐year survival varied widely between the histologic types when comparing tumor sites: 14.5% for SmCCHN versus 48.9% for SCCHN in the oropharynx. In propensity score matched analyses, the corresponding HR was 1.27 (95% CI, 1.15–1.40). CONCLUSION. Compared with SCCHN, SmCCHN carries a worse survival and is more likely to present with more advanced stage. IMPLICATIONS FOR PRACTICE. Small cell carcinoma of the head and neck (SmCCHN) is a rare subtype of head and neck cancer. In this Surveillance, Epidemiology, and End Results (SEER) data analysis, the characteristics and survival of SmCCHN are compared with those of the common squamous cell carcinoma of the head and neck. Results show that SmCCHN carries a worse prognosis and tends to present at a more advanced stage; SmCCHN also is ten times more likely to originate from the salivary glands. These findings may have implications for clinical practice, as location of the tumor may strongly associate with the pathologic diagnosis. If a SmCCHN is diagnosed, a disseminated disease is likely; hence vigilance in staging procedures is indicated.